A study of eight newly reported species of Chlorophyte and Eustigmatophyte, Korea - Song, Mi Ae; Lee, Ok-Min (Journal of Ecology and Environment, 2014)
In this study, aquatic and aerial algae were collected in various environments in Hongcheon-river of Gangwan-do between December 2011 and June 2012, with the aim of adding newly described genera and species to the Korean flora. As a result, five genera and eight species were recorded for the first time in Korea. These newly recorded genera and species were Cylindrocapsa geminella, Leptosira mediciana, Pseudendoclonium basiliense var. brandii, Stichococcus minor, S. deasonii, Eustigmatos polyphem, Nephrodiella lunaris, and Xanthonema exile. The eight taxa identified in this study mostly corresponded to their reported morphological characteristics. However, some differences from previous published descriptions were found; N. lunaria, reported to be an aquatic species in a previous study, was found to be an aerial algae inhabiting on rocks and mosses. Cylindrocapsa geminella was found to transform into attached or planktonic algae depending on the environmental condition, and the cell wall was found to be changed. Likewise, E. polyphem was seen to change cell-shape or chloroplast color according to the environment.